Endorsement: Its Role In Buying Interest In Cosmetics - Kurnia Khafidhatur Rafiah; Za’imah Humairah; Andreas Recki Prasetyo (CV Putra Publisher, 2024)
The rapid development of technology has led to lifestyle changes, demanding humans to balance and adapt quickly. Likewise, for business practitioners, there are many modern marketing techniques emerging and proving effective in attracting consumer interest, tempting business practitioners to utilize them. Such as leveraging the opinions of others using social media to create consumer purchase interest. This research investigates the role of Instagram endorsements in stimulating consumer purchase interest in Somethinc cosmetic products. Attitude scale statements were provided to 105 respondents, who are Instagram users currently, previously, or planning to use Somethinc cosmetics, predominantly women aged 21-25 years old, to determine the extent to which Instagram endorsements play a role in arousing their purchase interest. The analysis method used is simple linear regression. The research results indicate a positive and significant role of Instagram endorsements in stimulating consumer purchase interest. Respondents revealed that the Endorsers' ability to convey product information is the most dominant factor that makes them want to know and seek further information about the products in question, followed by the relevance of the information conveyed, and the credibility of the Endorsers.